HUKUM DAN DAMPAK PSIKOLOGIS PENELANTARAN ISTERI OLEH SUAMI MENURUT ULAMA DESA CIHERANG KECAMATAN BANJARSARI KABUPATEN CIAMIS - Ibnu Taufan Mulyana; Sumadi Sumadi; Madiha Dzakiyah Chaerunnisa (Fakultas Syari'ah | Institut Agama Islam Darussalam | IAID | Ciamis, Jawa Barat, Indonesia, 2018)
In living a married life, there are always problems that arise and can trigger the desire and courage of a husband to choose to leave a wife and child or what is called household abandonment. This article mainly focuses on the views of the Ulama of Ciherang Village, Banjarsari District, Ciamis Regency, about the Psychological Impacts of neglecting their wives by their husbands. This study uses a qualitative method. The application of this method includes the stages of data collection through observation, interviews, documentation, data analysis and research reports. This study also uses an anthropological approach. This research is the basis for understanding human behavior according to cultural backgrounds and beliefs humanely. The Ulama of Ciherang Village is of the view that it is a legal sin for a husband who abandons his wife without giving any news even though a husband loves the birth support, because basically it is not only the physical income that must be fulfilled but also the internal income. The inner life does not have to be intimate, but also gives advice, comforting the wife is also part of the inner support. If indeed the wife sincerely accepts it then there is no problem, otherwise the husband will sin. The psychological impact of the wife arising from her husband's abandonment in Ciherang Village, Banjarsari District is as follows: (a). The wife feels a deep hurt, resentment and hatred as a result of being neglected by her husband for more than 2 years. (b). The habit of crying because the incident seemed unexpected. In other words, she still did not believe her husband left her without giving news. And this has an effect on reduced appetite. (c). The wife feels hopeless in living with her child because she is depressed by circumstances. (d). Feeling embarrassed when leaving the house because it is the topic of the neighbors' conversation. (e). The wife more often tells about her family problems to other people, be it neighbors or relatives, this is only to vent her feelings of annoyance to her husband.